A fuzzy ANP approach to shipyard location selection - Guneri, A. F.; Cengiz, M.; Seker, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
It is the first duty of investors to transform financial resources into investments in the right places at the right times and earn benefits. However, where to invest and how to invest is always a risky and complicated problem. The decision which will be made under a variety of factors might result in a terrible mistake if it is not felicitous. It is necessary to utilize scientific methods when deciding to make these types of complicated investments which can cause large financial losses. Analytical network process (ANP) can show us the best alternative based on different criteria from a variety of alternatives. However, the network structure should model the actual in a very good way. Analytical network process will give us the best result in span after the correctly built network structure's comparisons are made correctly. It is important to design the structure flexibly in this work in order for it to lead to improvements. Shipyard location is selected in this work which provides reference to investors based on numerical and solid essences. At the end, the study has received a successful application with the help of expert people and the correct fuzzy analytical network process's success over the criteria which have a close relationship with each other. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Analytic network process; Fuzzy logic; Multi-criteria decision analysis; Location selection; DEVELOPMENT PROJECT SELECTION; AHP; MODEL; Computer Science; Engineering; Operations Research & Management Science